Clinical Characteristics of Three Cases with SAMD9/SAMD9L Gene Mutations - ZHU Ke; SUN Bijun; WANG Wenjie; ZHOU Qinhua; LIU Luyao; HOU Jia; WANG Xiaochuan; SUN Jinqiao (罕见病研究)
Mutations in the SAMD9 and SAMD9L genes are associated with MIRAGE syndrome and ATXPC syndrome, respectively. This study reports the clinical characteristics and genetic analysis of one case with SAMD9 mutation (c.3809T > A, p.F1270Y) and two cases with SAMD9L mutations (c.2675T > G, p.M892R; c.1096T > G, p.F366V and c.4517T > C, p.L1506p), none of which have been previously reported. All patients presented with recurrent infections, growth retardation, and myelodys-plasia, with varying degrees of involvement of multiple systems, including respiratory, gastrointestinal, immune, endocrine, neurological, and reproductive systems. In terms of treatment, two patients underwent regular intravenous immunoglobulin and their clinical symptoms improved, while one patient had a favorable recovery following hematopoietic stem cell transplantation at the age of 1 year and 5 months of age. SAMD9/SAMD9L gene mutations, therefore, chould be considered in children with recurrent infections, myelodysplasia, pancytopenia, and growth retardation. Early genetic testing is crucial for timely diagnosis and treatment, which may improve patient outcomes.